PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MELALUI PEMBELAJARAN KOOPERATIF TIPE TEAM-ASSISTED INDIVIDUALIZATION DAN NUMBERED HEAD TOGETHER - Septya Giartianti; E Elvis Napitupulu (Universitas Negeri Medan, 2018)
This study aims to determine whether are differences in problem solving skills of mathematics students using cooperative learning type TAI and NHT in class VII SMP Negeri 3 Pulau Rakyat. This type of research is quasi experiment. The population in this study is all students of grade VII semester 2 SMP Negeri 3 Pulau Rakyat consisting of 5 classes with total 160 students and the sample of this study are VII-1 and VII-3 as many as 64 students. The required dara is obtained by using the students’ math problem solving test in the form of a description of 4 question. From the results of data analysis obtained the average test results of students mathematics problem solving abilities through cooperative learning type TAI is 27,28 with varians 2,65 and the average test result of students’ mathematics problem solving abilities through cooperative leraning type NHT is 22,25 with varians 3,28. To test hypothesis used t test, from the calculation results obtained tcount with the test reject Ho and accept Ha if tcount 1,6697 so it looks that tcount is not reside in the Ho accetance area which means Ho rejected and Haaccepted or in other words there are differences problem solving ability of mathematics students using cooperative learning type TAI and NHT in class VII SMP Negeri 3 Pulau Rakyat. Keywords: Mathematical Problem Solving Abilities, TAI, NHT